Efficient growth of vertically-aligned single-walled carbon nanotubes combining two unfavorable synthesis conditions. (May 2019) - Liu, Ming; An, Hua; Kumamoto, Akihito; Inoue, Taiki; Chiashi, Shohei; Xiang, Rong; Maruyama, Shigeo
Abstract: We demonstrate an unexpected recipe for the efficient synthesis of vertically-aligned single-walled carbon nanotubes (SWCNTs). The growth of high-density arrays is achieved by combining two unfavorable conditions: low temperature and mono-metallic Co catalyst, neither of which was previously found to be effective for the synthesis of SWCNT forest. As a result of this new recipe, the as-synthesized SWCNTs have a narrower diameter distribution than those obtained in previous studies, with 85% of the SWCNTs between 1.6 and 2.4 nm. Meanwhile, we utilize our recently established transmission electron microscopy (TEM) technique to characterize this monometallic Co catalyst directly on SiO2 . Nanoparticles in a 600 °C reaction are confirmed to be smaller, denser and more uniform than those formed at high temperatures. Our technique further allows to image catalyst at high temperatures, by which Ostwald ripening is visualized at a single particle level. In addition, in situ electron diffraction and imaging confirm that monometallic Co catalyst remains as a solid phase even at 800 °C. The discovery of new growth recipe increases the compatibility of synthesizing SWCNT onto other substrates. The new TEM technique provides experimental evidence for some long-standing hypotheses of catalytic particles and is capable of guiding the design of new catalysts. Graphical abstract: Image 1